Publishers on books in Women's Studies. - Smith, Catherine F. (Women's Studies, 1975)
Discusses the findings of a report responding to a call for surveys of trends in publishing concerning women that was sent out by the participants of a Modern Languages Association convention workshop in 1973. Objective of the report; Inclusion of full-length scholarship concerning women from any academic specialization in the definition of works in women's studies.